Association Of Stress and Prakriti: A Conceptual Review - Parmar, Neha; Rajan, Sujata (International Research Journal of Ayurveda & Yoga, 2021)
Prakriti is an expression of one’s own constitution. It is an expression of body functions, in the form of morphology, physiology, behavior of an individual. From the very time of conception, some persons are having equilibrium of Vata, Pitta And Kapha while others are seen Vatala, Pittala And Slesmala (having predominance of Vata Or Pitta Or Kapha). It is an important concept of Ayurveda that explains individuality. Acharya Charaka has mentioned Prakriti in one of the Parikshya Bhava. Acharya has quoted in the very beginning- “Purushampurusham vikshyam”. Though two individuals are of same Jati, Kula, Vaya etc. still they may not have same characters, similarly even if their Sara, Samhanana, Pramana, Satmya etc. are similar they will be of entirely different personality which is observed in the society among various individuals. In this competitive era, everyone is suffered from stress in his/her phases of life. Stress is the prime and important causative factor behind any disease. List of diseases either Sharirika or Mansika, all having a stress factor behind. But no one focus on that so the present conceptual review focus on the stress and prakriti association and ultimately helping him to keep stress-induced diseases away.